Wood structure, xylem functionality and growth of six Salix clones in two sites with different environmental stress in Argentina - Loval, Sabrina Anahí (2018)
The aims of the study were to evaluate the effects of abiotic stress (plantation site) and genotype (clone) on the wood anatomy and density of six Salix (willow) clones at three ages (2, 7, and 12 years), and the impact of these effects on the theoretical xylem hydraulic conductivity (Ks) and growth. The clones studied were ´Ragonese 131-25 INTA´, ´Ragonese 131-27 INTA´ and “250-33” (originated from crosses between Salix babylonica and S. alba), ´Barrett 13-44 INTA´ and “NZ 26992” (originated from crosses between S. matsudana and S. alba), and the clone S. babylonica var. sacramenta ´Soveny Americano´. They were planted in two sites of the province of Buenos Aires, Argentina, with different abiotic stress: i) the Paraná River Delta, a site with recurrent floods, and ii) a continental site with lower water availability and no floods. The vessel morphometry, wood density, Ks, and current annual increments at the three ages were determined. The clone x site interaction was the source of variation with greatest impact, being this significant for vessel diameter, Ks, wood density and growth. This means that, depending on the type of stress at the plantation site, the clones responded differently, showing differences in their structure, functionality, and wood production. The results showed that the clones Soveny Americano and 26992 were better suited to stress by flood, whereas clones 131-25, 131-27, 250-33 and 13-44 were better adapted to moderate drought conditions, with responses at the level of the xylem and wood density, and therefore at the level of wood production.